New Limonoid from Chisocheton macrophyllus: Isolation, Synthesis, Molecular Docking Studies, and Cytotoxicity against Cancer Cells - Muhammad Badrul Huda; Nurlelasari Nurlelasari; Faris Hermawan; Wahyu Safriansyah; Unang Supratman; Yudha Prawira Budiman (Pandawa Institute, 2026)
Dysobinin is a naturally occurring limonoid and a type of triterpenoid, which shows certain efficacy, although its prospects in the field of pharmacology are still limited. Therefore, this study aimed to improve the pharmacological properties of dysobinin through structural rearrangement. A 56% yield was obtained using Selectfluor to convert dysobinin into a novel molecule, specifically 22α-carboxyacid-dysobinin (5). Compared to the other compounds, 22α-carboxyacid-dysobinin (5) exhibited significantly higher cytotoxicity against human epithelial tumor (HeLa) and B16-F10 cancer cells. However, this compound 5 exhibited the lowest cytotoxicity against MCF-7 cancer cells. Subsequently, a docking study showed that compound 5 had binding energies of -9.61, -7.81, and -6.08 kcal/mol for EGFR, Bcl-2, and Tyrosinase, respectively. In the prediction of pharmacokinetic parameters, compound 5 fulfilled the minimum standard parameters for the ADMET properties. Therefore, compound 5 may be considered a promising lead compound for anticancer development, warranting further optimization and validation.